Designing Flow-Based Chatbot as Student Information Service Center - Arifiyanti, Amalia Anjani; Daniar, Ivan Faiz; Permatasari, Reisa; Najaf, Abdul Rezha Efrat (Nusantara Science and Technology Proceedings, 2023)
Universities strive to enhance public services to continually elevate user satisfaction. One critical aspect of public service is the accessibility and transparency of information, particularly in ensuring that students can easily access relevant information, contributing to heightened satisfaction with the university. However, while fostering openness and accessibility, adequate resources are essential to manage the surge in information requests from students. Chatbots emerge as a viable solution for disseminating information on academic activities, providing easy accessibility unhindered by temporal or spatial constraints at UPN "Veteran" Jawa Timur. In the initial phase of chatbot design, delineating the flow of user queries and corresponding bot responses is imperative. Questions, organized in a flow-based manner, are derived from a dataset of student queries related to academic policies. Extracting prevalent topics from both the question dataset and academic policy regulations at UPN "Veteran" Jawa Timur resulted in four overarching question topics: Implementation of Education, Learning Beyond the Study Program, Assessment and Evaluation of Learning Outcomes, and Academic Violations. The Conversational Flow Diagram is crafted based on these topics, serving as the foundational pattern for the chatbot. The test results affirm the chatbot's success in accurately presenting all designated flows, thereby furnishing users with pertinent information.